Modeling of Indoor Wave Propagation Models from 1 G Hz to 10 G Hz - Othman , A. R,; Hamidon, A. H; Wasli , C; Mustaffa , M. F; Ting, J. T. H (2010)
This paper presents the modeling of indoor wave propagation from 1 GHz to 10 GHz. Several obstacles such as partition, whiteboard, and door have been tested and measured their losses compare to line of sight. Horn antennas have been used as transmitter and receiver. An average attenuation between of this obstacle between 1.5 dB to 3.0 dB has been observed. Prediction model for this indoor propagation has been presented using suitable software. Finally, results, discussion, conclusions and further work are given.